EVALUASI KONDISI STRUKTUR JEMBATAN DENGAN PENGUKURAN TEGANGAN DAN REGANGAN AKIBAT BEBAN LALU LINTAS AKTUAL - Setyo Hardono (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
The background of this paper is the problem of evaluation of the bridge structural condition during service life. The evaluation becomes important in determining the bridge capacities or influence of cyclic load to the bridge structure. The assessments of these problems often appear. Measurement of tension and strain of bridge structural elements are essential in technical discussions to assess the evaluation of actual bridge capacity. The tension and strain instrumentation are placed at critical section of the element. Strain data and tension are measured during passage of vehicles. The recorded data will contain maximum, minimum and average tension and strain measurement during testing. Evaluation of strain and tension data will reveal the pattern of tension cycles that occurred during the bridge testing by vehicle passage loading.